Why despite the curriculum (life skills/orientation) offered by the department of education in schools, teenagers in Mthatha dictrict of the Eastern Cape continue to contract and die from HIV/AIDS, continue to be vulnerable to STIs and teenage girls continue to fall pregnant - Mcutshenge, Nomna Nombulelo Pheolla (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.